Anatomy of urinary continence and neurogenic incontinence. Issue 2 (March 2009) - Golomb, Jacob; Chertin, Boris; Mor, Yoram
The urinary bladder has a dual function –– urine storage and periodic emptying. During storage the detrusor muscle is relaxed and the sphincteric mechanism is active to prevent urinary leakage while the bladder becomes progressively distended. In the voiding phase the pelvic floor and external urinary sphincter relax, the detrusor muscle contracts and bladder emptying ensues. The mechanism of these repetitive events depends on adequate detrusor muscle contraction and relaxation, competence of ureterovesical junctions and the urethral sphincter, as well as a complex central and peripheral neural control of both the smooth- and striated-muscle systems.